Cattle production analysis using a steady state model - Caputi, P.; Murguía, J. M. (Agrociencia Uruguay, 2003)
Uruguayan cattle raising interrupted in 1990's its historical stagnation with a significant extraction rate increase. The central purpose of this work was to inquire if technological changes in breeding and finishing were coherent with new aggregated production levels observed. To investigate this problem a theoretical stationary state Overlapping Generation Model (OLG) was developed. This OLG was used to estimate the stationary state extraction rate with a given breeding and finishing efficiency. The deducted function easily permits to characterize a country's productive situation and compare it with other countries, and with its different possible growing extraction rate paths. At this new arisen point in 1990's, the extraction rate was between 19 and 20 percent. This level is timely sustainable if new efficiency levels achieved at breeding and "finishing" persist. To project future growing extraction rate paths, its necessary to estimate the county's optimal breeding-finishing combination.